2016
DOI: 10.1371/journal.pone.0149957
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Coxiella burnetii Reveals Extensive Cell Wall Remodeling in the Small Cell Variant Developmental Form

Abstract: A hallmark of Coxiella burnetii, the bacterial cause of human Q fever, is a biphasic developmental cycle that generates biologically, ultrastructurally, and compositionally distinct large cell variant (LCV) and small cell variant (SCV) forms. LCVs are replicating, exponential phase forms while SCVs are non-replicating, stationary phase forms. The SCV has several properties, such as a condensed nucleoid and an unusual cell envelope, suspected of conferring enhanced environmental stability. To identify genetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 120 publications
(154 reference statements)
6
70
0
Order By: Relevance
“…Structural rigidity in SCV-form Coxiella is partially conferred by a thick peptidoglycan, and it has recently been shown that this is characterised by an abundance of LD-transpeptidase-mediated 3-3 peptide cross-links (Sandoz et al, 2016).…”
Section: Coxiella Burnettiimentioning
confidence: 99%
“…Structural rigidity in SCV-form Coxiella is partially conferred by a thick peptidoglycan, and it has recently been shown that this is characterised by an abundance of LD-transpeptidase-mediated 3-3 peptide cross-links (Sandoz et al, 2016).…”
Section: Coxiella Burnettiimentioning
confidence: 99%
“…Genes associated with SCV differentiation are regulated by RpoS. The large cohort of RpoS-regulated genes directed us to focus on four subsets of genes that were previously shown to be developmentally regulated during SCV differentiation (25). Thirty-two SCV-associated genes were related to arginine transport/metabolism, cell wall remodeling, and responses to general and oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, unless PG is purified from intracellular bacteria, it is not possible to definitively conclude the selective pressure that the host has imposed on intracellular pathogens. As my group and a few others have shown (Mahapatra et al, ; Packiam et al, ; Pilhofer et al, ; Quintela et al, ; Sandoz et al, ), it is possible to isolate PG directly from the infected cells and this information is crucial to understand these host‐pathogen interactions. Another fascinating fact is the presence of PG containing D‐amino acids in moss chloroplasts (Hirano et al, ).…”
Section: Future Directionsmentioning
confidence: 96%
“…This, therefore, continues to be the major obstacle when attempting to purify PG from a reduced number of bacteria, as it is the case in most in vitro and in vivo infection models with intracellular bacterial pathogens and endosymbionts. The few successful cases of muropeptide characterization include those of the obligate bacterial pathogens Chlamydia trachomatis (Packiam, Weinrick, Jacobs, & Maurelli, 2015), Coxiella burnetii (Sandoz et al, 2016), and Mycobacterium leprae (Mahapatra, Crick, McNeil, & Brennan, 2008); the facultative intracellular pathogen Salmonella enterica serovar Typhimurium (Quintela, Pedro, Zollner, Allmaier, & Garcia-del Portillo, 1997); and the Acanthamoeba spp. endosymbiont Protochlamydia amoebophila (Pilhofer et al, 2013).…”
Section: An P G S Truc Ture and Enz Ymology B E Monitored In Intrmentioning
confidence: 99%
See 1 more Smart Citation